(832) Notes in The Inventory Theory ملاحظات في نظرية المخزون - Makary, Nadia (The Institute of National Planning, 2024)
Inventories are stocks of goods stored for specific reasons, despite the storage costs and the capital that could be invested elsewhere. There are various reasons for maintaining inventories. Often, they are held due to economies of scale in production or seasonal fluctuations in the prices of raw materials used in production. Uncertainty in future demand and the time lag between placing orders and receiving goods are also strong reasons for holding inventories.